Reposisi Peranan Pemeriksaan/Audit Dalam Mengawasi Program Pemerintah - Sarjono Sarjono (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
Changes in boards of BPK followed by a change of strategic audit plan. Board’s current period brings big issues that are different from the previous period, the audit associated with the issue of welfare or prosperity. This study aims to determine whether the BPK had and the need to reposition the role of major issues related to the changes brought by the new boards. This research is qualitative content analysis method with the object of study are audit strategic plan, a draft audit strategic plan, and IHPS from 2008 to 2014. By using the approach of the six key elements offered by Ryan, et al (2007), the results showed that the BPK (boards and auditors) has realized some key elements as the form of the repositioning, such as the strengthening of strategic value, learning capabilities and strategic flexibility, an adequate understanding of audit entities, and the top management commitment. However, the results also show that auditors still need to have an understanding of the sensitivity of the audit entity when conducting the audit assignment and must be open to receive criticism from the outside, able to recognize the value and appropriateness of the strategy of the audit institution other, have a deep understanding of current external issues.